On improving emergency preparedness and management with Delphi - Laakso Kimmo (Canada, 2022)
An emergency brings together a group of individuals who often represent different organizations, resources, and roles. In order to be able to make the right decisions, individuals need to understand each other although they may be from different lines of business. In our research the target is to stress the importance of a common language in emergency management. Our plan is to gather a group representing the authorities, i.e. public sector actors, and a group representing companies, i.e. private sector actors, to communicate with the Delphi method on possible differences in the language used in different lines of business. The aim of this paper is to discuss the possibilities of using the Delphi method to make improvements to emergency management and to evaluate which kinds of organizations should be represented in our Delphi panel. This paper forms a part of a larger research study, the results of which will be useful, for example when improving the interoperability of management and communications systems.
ISCRAM 2012 Conference Proceedings: Book of Papers